mudelgen: A Tool for Processing Mutant Operator Descriptions - Simão, Adenilso da Silva; Vincenzi, Auri Marcelo Rizzo; Maldonado, José Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2002)
Mutation Testing is a testing approach for assessing the adequacy of a set of test cases by analyzing their ability in distinguishing the product under test from a set of alternative products, the so-called mutants. The mutants are generated from the product under test by applying a set of mutant operators, which systematically yield products with slight syntactical differences. Aiming at automating the generation of mutants, we have designed a language — named MuDeL — for describing mutant operators. In this paper, we describe the mudelgen system, which was developed to support the language MuDeL. mudelgen was developed using concepts that come from transformational and logical programming paradigms, as well as from context-free grammar and denotational semantics theories.